Beverage-specific patterns of 5+ alcoholic drink consumption by young adults in the U.S. (February 2017) - Stern, Stephanie A.; Terry-McElrath, Yvonne M.; Patrick, Megan E.
Abstract: Young adult binge drinking prevalence has been widely researched. However, beverage-specific binge drinking rates for beer, liquor, wine, and wine coolers have not yet been documented for this age group. This study examines consumption of specific beverages (i.e., 5+ drinks in a row in the past two weeks) by young adults aged 19/20. Data from the national Monitoring the Future study were collected one or two years after high school from 2004 to 2014 ( n  = 2004). Logistic regression was used to examine associations between beverage-specific 5+ drinking and gender, race/ethnicity, parent education, college status, and cohort year. Overall 5+ drinking in the past two weeks was reported by 31.4% of young adults. Beverage-specific 5+ drinking was most common with liquor (22.6%) and beer (22.4%), followed by wine (4.5%) and wine coolers (3.0%). Men were more likely than women to engage in 5+ drinking with beer and liquor; women were more likely than men to do so with wine and wine coolers. Beverage-specific patterns differed by college attendance. Compared to four-year college students, two-year college/votech students were less likely to have 5+ drinks of liquor or wine, and more likely to have 5+ wine coolers; those not in college were less likely to have 5+ drinks of liquor and more likely to have 5+ wine coolers. Differences in beverage-specific 5+ drinking by gender and college enrollment suggest that intervention efforts should focus on the beverages that are most commonly consumed at high levels within specific early young adult populations. Highlights: We examined beverage-specific 5+ drinking among U.S. young adults. 5 + drinks was most common with liquor and beer, followed by wine and wine coolers. Men were more likely than women to have 5 + drinks of beer and liquor. Women were more likely than men to have 5 + drinks of wine and wine coolers. 5 + drinking differed by college enrollment (4-year, 2-year/votech, no college).